Too many cooks could spoil the broth: choice overload and the provision of ambulatory health care - Helmut Herwartz; Christoph Strumann (International Journal of Health Economics and Management, 2024)
Abstract Patient empowerment calls for an intensified participation of (informed) patients with more treatment opportunities to choose from. A growing body of literature argues that confronting consumers with too many opportunities can lead to a choice overload (CO) resulting in uncertainty that the selected alternative dominates all other options in the choice set. We examine whether there is a CO effect in the demand for ambulatory health care in Germany by analyzing the association of medical specialists supply on so-called patients' health uncertainty. Further, we investigate if the CO effect is smaller in areas with a higher density of general practitioners (GPs). We find that patients who live in an area with a large supply of specialists are subject to a CO effect that is expressed by an increased health uncertainty. The coordinating role of GPs seems to be effective to reduce the CO effect, while preserving free consumer choice.
Additional information: C21;C23;D12;D83;I12;I18
Keywords: 330; Choice overload; Patient choice; Health care coordination; Spatial distribution of health services